Histopathologic Examination of Trabecular Meshwork Changes After Trabecular Bypass Stent Implantation. Issue 7 (July 2018) - Capitena Young, Cara E.; Ammar, David A.; Seibold, Leonard K.; Pantcheva, Mina B.; SooHoo, Jeffrey R.; Kahook, Malik Y.
Abstract : Purpose: The purpose of this article was to evaluate how human trabecular meshwork (TM) is influenced by the chronic presence of trabecular bypass implants. Methods: Human TM samples were obtained intraoperatively from 3 patients who had previously undergone implantation of a trabecular micro-bypass stent. Trabecular strips were obtained with a goniotomy blade from areas directly adjacent to the stent after stent removal. Tissue samples were preserved, processed, cut, and stained according to standardized laboratory protocol. Harvested samples were compared with human cadaveric TM from an eye without ocular disease as well as TM obtained from a glaucomatous eye without prior stent placement. Results: In all samples, a significant increase in the amount of fibrous material compared with cellular material was noted when compared with controls. In a single strip, a basement membrane-like structure was noted, which correlated with a semiopaque membrane noted intraoperatively overlying the stent and adjacent TM. Further, TM cells were absent from areas adjacent to the stent implantation site with related collapse of collagen beams. Conclusions: These findings indicate that inflammatory and fibrotic changes are present surrounding the device with clear differences noted when compared with both healthy and glaucomatous controls. These changes suggest a possible etiology for device failure over time. Further studies are necessary to tease out differences in TM tissue reaction to various implant materials as well as to make comparisons to procedures that excise TM.